Probabilistic Static Voltage Stability of Power System with Integration of PV Generators using Monte Carlo Simulations: Probabilistic Static Voltage Stability of Power System - Krismanto, Awan Uji; Khairullah, Hafizhul Ayyasi; Sulistiawati, Irrine Budi; Lomi, Abraham; Sarkar, Dipu (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
As a renewable source, the uncertainties and intermittencies of solar irradiance have become the main concern in developing and integrating such power generation into an electricity network. In power system operation, it is important to maintain a stable voltage profile under random power injection from renewable power generations. The effect of photovoltaic (PV) power plants on the static voltage stability of the interconnected power system is presented in this paper. The probabilistic study was conducted through Monte Carlo Simulation (MCS) to investigate the fluctuation of voltage profiles under uncertain power injection from PV power plants. The standard test system of IEEE 14 bus and practical test system of Lombok, West Nusa Tenggara electricity network are investigated. It was noticed that the installation of a photovoltaic power plant affected the voltage profiles. The fluctuated condition of power injection from PV power plant resulted in more fluctuation of voltage profiles as indicated by higher standard deviation values. Moreover, distributed location of the PV power plant also influenced the circumstances of voltage fluctuation, providing less fluctuated condition of voltage profiles. Eventually, it can be observed that the voltage fluctuation would influence the static voltage stability of the interconnected power system.